Partisipasi Masyarakat dalam Peningkatan Kualitas Pendidikan Agama Islam (PAI) di Madrasah - Rusyaid, Rusyaid (Al-Riwayah : Jurnal Kependidikan, 2020)
The community is a group unit that is closely related and has the same interests. Society is seen as the basic capital of development, which if we develop it, it will contribute greatly to development. His involvement in implementing educational policies is the manifestation of the use and utilization of basic development capital. The community as service users and educational institutions has an obligation to develop and maintain the sustainability of the educational process. Ordinary people may mean that participation is a form of contribution, role or participation of someone in a certain activity. Participation cannot be interpreted only as the formality of someone's participation, but there must be concrete evidence or concrete action that the person or group helps to make a particular activity successful. Community participation in improving the quality of madrasah educational institutions is needed. Through the participatory method, encouraging everyone into a group process regardless of age, gender, social status or educational background.